Ethnomathematics on bamboo woven crafts in Dusun Brajan, Yogyakarta and implementation in mathematics learning - Cyrenia Novella Krisnamurti; Chintia Kurnia Dewi (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2023)
. Indonesia is a country that is rich in natural and cultural resources. One of the cultures they have is fine arts. Fine art is one of the diverse cultures. This study examines one of the fine arts from Yogyakarta, namely woven bamboo. The famous woven bamboo handicraft industry comes from Dusun Brajan, Sendangagung, Kecamatan Minggir, Kabupaten Sleman, Yogyakarta. This study aims to determine the history of bamboo weaving activities, mathematical fundamental activities and implementation of bamboo weaving in Dusun Brajan in learning mathematics for junior high school students. The research method used is descriptive qualitative research with an ethnographic approach that aims to describe and assess the pattern of the bamboo craftsman group in Dusun Brajan. Data collection methods used were observation, documentation and interviews with the administrator of the Desa Wisata Brajan and the Dusun Brajan bamboo weaving craftsmen. The results of this study indicate the beginning of the development of woven bamboo crafts until now it has become a well-known craft centre. Through this woven bamboo, students can learn six basic math activities: counting, finding, measuring, designing, playing, and explaining. Implementation in learning mathematics in junior high schools is a contextual problem that can be used as discussion material for students.